Fabrication and characterization of polycaprolactone-based nanofibrous scaffolds for neuronal tissue regeneration - Elnaggar, Manar Ahmed (AUC Knowledge Fountain, 2020)
Recent advances in regenerative medicine have given hope in overcoming and rehabilitating complex medical conditions. In this regard, biomaterial scaffolds are employed to support cellular adhesion, elongation, and growth, thus promoting sound healing and restoration of function after trauma. The biopolymer poly-ε-caprolactone (PCL) may be a promising candidate for tissue regeneration, in this regard, although lacking essential bioactivity. The present study used PCL nanofibers (NFs) scaffold decorated with the extracellular matrix proteins fibronectin and laminin for neuronal regeneration. The potential for the combined proteins to support neuronal cells and promote axonal growth was investigated. Two NFs scaffolds were produced with concentrations of PCL: 12% or 15%. Under scanning electron microscopy, both scaffolds evidenced uniform diameter distribution in the range of 358 nm and 887 nm, respectively, and greater than 80% porosity. The Brunauer–Emmett–Teller test confirmed that the fabricated NFs mats had a high surface area, especially for the 12% NFs with 652 m2/g compared to 254 m2/g for the 15% NFs. Therefore, the 12% NFs was selected for further study. The proteins of interest were successfully conjugated to the PCL scaffold through chemical carbodiimide reaction as confirmed by Fourier-transform infrared spectroscopy. Moreover, the in-vitro degradation test showed slow degradation rate. The addition of fibronectin and laminin together was shown to be the most favorable for cellular attachment and elongation of neuroblastoma SH-SY5Y cells. Confocal light microscopy revealed longer neurite outgrowth, higher cellular projected area, and lower shape index for the cells cultured on the combined proteins conjugated fibers, indicating enhanced cellular spread on the scaffold. This preliminary study suggests that PCL scaffolding conjugated with matrix proteins can support neuronal cell viability and neurite growth, suggesting potential application in cases of spinal cord injury (SCI).